The Klondike Nugget excursion party on the deck of the steamboat PROSPECTOR on their trip from Dawson to Stewart, Yukon Territory, 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.193 As an expression of good fellowship, the staff of the Klondike Nugget newspaper, their wives and friends were invited to take a pleasure trip to the mouth of the Stewart River 75 upstream from Dawson. [Meed journal: "The excursion trip from Dawson to Stewart given as a token of good will to the staff of the Klondike Daily Nugget, their wives and friends. My wife is in the front near center with the child of a member of the party."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number